Prenatal care and human rights: Addressing the gap between medical and legal frameworks and the experience of women in Brazil. - Camila Brito Rodrigues; Erika Barbara Abreu Fonseca Thomaz; Rosângela Fernandes Lucena Batista; Pía Riggirozzi; Dina Stefany de Oliveira Moreira; Laura Lamas Martins Gonçalves; Zeni Carvalho Lamy (PLoS ONE, 2023)
Access to quality and affordable healthcare is central to the fulfilment of women's reproductive and sexual health needs and rights. For this reason, the World Health Organization declared access to appropriate healthcare services during pregnancy and childbirth a fundamental women's right. Prenatal care is a recognized human right to women's health in Brazil, as declared by the 1988 Constitution and many Brazilian policies. However, implementing the rights to health in Brazil presents a fundamental performance gap between legal rights and their delivery concerning reproductive health. Through extensive fieldwork including focus groups, interviews with women and participate observation in two municipalities in northeastern Brazil, this article addresses these issues and explores women's lived experience of access to and their fulfilment of the right to health regarding prenatal healthcare. We offer and account of the experience of women regarding what they identified as barriers that trample their right to health, that is: a) limited personnel and medical equipment as a perception of neglect; b) timely delivery of services: time matters for perception and experience of rights; c) misinformation as a barrier to the exercise of health rights; and d) socioeconomic barriers. These barriers particularly affect the right of women in rural communities, with lower socioeconomic levels and education, as well as brown and black women, from an intersectionality perspective, who are already at greater health risk and inadequate prenatal care. As such, we argue there is a performance gap between what the normative and legal frameworks encourage the health system to do and what the system actually provides in terms of access, equality, respect and continuity of treatment amongst certain groups in society whose right to health are denied while their health risks increase.